2016
DOI: 10.3389/fnbeh.2015.00360
|View full text |Cite
|
Sign up to set email alerts
|

Is it Worth the Effort? Novel Insights into Obesity-Associated Alterations in Cost-Benefit Decision-Making

Abstract: Cost-benefit decision-making entails the process of evaluating potential actions according to the trade-off between the expected reward (benefit) and the anticipated effort (costs). Recent research revealed that dopaminergic transmission within the fronto-striatal circuitry strongly modulates cost-benefit decision-making. Alterations within the dopaminergic fronto-striatal system have been associated with obesity, but little is known about cost-benefit decision-making differences in obese compared with lean in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 97 publications
(119 reference statements)
2
11
0
1
Order By: Relevance
“…In contrast to ACC, premotor areas and insular cortex that encode arousal or salience (Bartra et al 2013;Rangel and Clithero 2013). Similar to other studies of effort-based decisions (Burke, Brunger, et al 2013;Mathar et al 2016), our design included an effort task where the participants did not reach the target goal in all of the effort trials. We accounted for this uncertainty component (probability of not making the goal) in our model, yet we acknowledge that future designs should separate between these components.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to ACC, premotor areas and insular cortex that encode arousal or salience (Bartra et al 2013;Rangel and Clithero 2013). Similar to other studies of effort-based decisions (Burke, Brunger, et al 2013;Mathar et al 2016), our design included an effort task where the participants did not reach the target goal in all of the effort trials. We accounted for this uncertainty component (probability of not making the goal) in our model, yet we acknowledge that future designs should separate between these components.…”
Section: Discussionmentioning
confidence: 99%
“…Although we are unable to tell the exact causal mechanism behind these associational patterns given the cross-sectional nature of our data, our finding that obesity predicts spinal diseases in the lower back but not in the cervical region provides more support for the mechanical-structural hypothesis than for metabolic or behavioral hypothesis. From a policy and management viewpoint, if the causal link between spinal disease and obesity is further substantiated by longitudinal and interventional studies, the health care expenditure associated with obesity might be even higher than the current estimates [83,84,85,86] and thus the cost-benefit ratio of obesity interventions might be more favorable that what has been estimated so far [87,88,89,90,91]. In other words, further research is needed where researchers employ longitudinal analyses or interventional studies examining whether weight loss leads to improvement of spinal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A newly published study suggests that obese people, compared with lean people, may be characterized by an abnormal cost–benefit decision‐making that undervalues the reward obtained from the engagement in physical exercise (Mathar et al . ). Unexpectedly, Mathar et al .…”
Section: Dynamic Exercisementioning
confidence: 97%
“…Unexpectedly, Mathar et al . () demonstrated that obese individuals, compared with lean individuals, are less willing to engage in physical effort to obtain high caloric sweet snack food rewards.…”
Section: Dynamic Exercisementioning
confidence: 99%
See 1 more Smart Citation